Tinjauan Ekonomi Syariah Terhadap Praktik Jual Beli Makanan Pada Rumah Makan Dapoer Bosdito Desa Plalangan Kecamatan Jenangan Kabupaten Ponorogo - Sugianto, Didik; Albanjari, Fatkhur Rohman; Rezqi Syakarna, Nugraheni Fitroh (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
This research was conducted with the aim of, first. To find out the Sharia Economic review of the sale and purchase agreement at the Dapoer Bos DITO restaurant on Bukit Ketekàn Plalangan Ponorogo. Second. To find out the Sharia Economic review of price setting at the Dapoer Bos DITO restaurant on Bukit Ketekàn Plalangan Ponorogo. The object of this research is all the components in the Dapoer Bos DITO restaurant on Bukit Ketekàn Plalangan Ponorogo. Data collection techniques through observation, interviews and documentation. The data collected regarding buying and selling practices at the Dapoer Bos DITO restaurant in Bukit Ketekàn Plalangan Ponorogo was analyzed qualitatively. The results of this research, first. A Sharia Economic Review of buying and selling contracts at the Dapoer Bos DITO Restaurant shows that the business prioritizes Islamic values such as honesty and transparency. The application of Islamic values in Dapoer Bos DITO's business increases trust and reputation in the eyes of customers. Second. A Sharia Economic review of pricing at the Dapoer Bos DITO Restaurant shows that the company considers production costs, competitor prices and profits in determining the price of the food sold. Dapoer DITO Boss is confident that with careful calculations, they can offer quality products at competitive prices. Dapoer Bos DITO business is in accordance with the provisions of Islamic law.